Recurrent Symptomatic Renal Stones Managed by Repeat Open Nephrolithotomy in a Rural Kenyan Hospital (American Journal of Medical Science and Innovation, 2024)
Kidney stone disease (nephrolithiasis, urolithiasis, and renal calculi) is characterized by the formation of both symptomatic and asymptomatic obstructive and non-obstructive calculi in the urinary tract. Calcium oxalate stones are the most common type, related to the consumption of large amounts of oxalate-rich foods. Other stones are made of calcium phosphate, hydroxyapatite, uric acid, cystine, and struvite. Urolithiasis is increasingly being reported in both urban and rural Kenya. Minimally invasive surgical treatment of symptomatic stones is the current standard of care, but open nephrolithotomy remains a viable option in selected patients. Nonetheless, the rates of stone recurrence remain high, increasing from 15% at 1 year to 50% at 10 years due to multifactorial risk factors. In this study, we report the case of a rural Kenyan patient who underwent the third open nephrolithotomy in 10 years for recurrent symptomatic stones and whose biochemical analysis has guided subsequent preventative dietary efforts against stone recurrence.